CO2 absorption in flat membrane microstructured contactors of different wettability using aqueous solution of NaOH - Constantinou, Achilleas; Barrass, Simon; Gavriilidis, Asterios (My University, 2018)
CO2 absorption in solutions of sodium hydroxide (NaOH) was performed in three membrane/mesh microstructured contactors: a single-channel polytetrafluoroethylene (PTFE) membrane contactor, a nickel mesh contactor and an eight-channel PTFE membrane contactor. A membrane/mesh was used to achieve gas/liquid mass transfer without dispersion of one phase within the other. The PTFE membrane consisted of a pure PTFE layer 20 μm thick laminated onto a polypropylene (PP) layer of 80 μm thickness. The pure PTFE layer contained pores of ~0.5 to 5 μm diameter and was hydrophobic, while the PP layer consisted of rectangular openings of 0.8 mm×0.324 mm and was hydrophilic. The nickel mesh was 25 μm thick and contained pores of 25 μm diameter and was hydrophilic. Experiments were performed with a 2 m NaOH solution and an inlet feed of 20 vol % CO2/N2 gas mixture. Numerical simulations matched reasonably well the experimental data. CO2 removal efficiency increased by increasing the NaOH concentration, the gas residence time and the exchange area between gas and liquid. Higher removal of CO2 was achieved when the PP was in the gas side rather than in the liquid side, due to lower mass transfer resistance of the gas phase. For the same reason, CO2 removal efficiency was higher for the eight-channel PTFE contactor compared to the nickel mesh contactor. Average CO2 flux was higher for the eight-channel contactor (8×10-3 mol/min·cm2 with PP on the gas side) compared to the nickel mesh contactor (3×10-3 mol/min·cm2) for the same gas and liquid residence times. The eight-channel PTFE membrane contactor removed around 72% of CO2 in 1.2 s gas residence time, demonstrating the potential for CO2 absorption using flat membrane contactors.
Keywords: CO2 capture; Membrane contactor; Microstructured contactor; NaOH absorbent